DISTRIBUTION OF NANOPLANKTON AND PICOPLANKTON AND THEIR TROPHIC INTERACTION IN THE ROSS SEA - MAVELLI, MASSIMO (Università degli Studi di Trieste, 2016)
Idiopathic nephrotic syndrome (INS) is the most common pediatric glomerulopathy (annual incidence: 2.7 cases/100.000 subjects aged 0-14 years), with a prevalence of 16 per 100.000 pediatric subjects. The therapy with prednisone is able to induce remission in 85-90% of children at onset, however, about 50% of them show frequent relapses, with the use of high doses of steroids, which involve inevitable side effects. To date, the optimal dose of steroids to be used in the first episode of INS has not been defined: the identification of biomarkers able to predict the sensitivity to glucocorticoids (GC) a priori could provide a useful tool to improve INS treatment and may be useful for developing an individualized therapy in these patients. With this background, the aim of the thesis was to identify the cellular and molecular markers associated with and predictive of outcome in pediatric INS. For this purpose, it has been developed a pharmacodynamic assay, to predict the sensitivity to GC in vitro and to assess the possible association between the clinical and the in vitro response in pediatric patients with INS. Preliminary studies were carried out to evaluate the associations between the clinical or the in vitro response and the presence of different genetic polymorphisms, the levels of expression of the GC receptor and of other proteins involved in the mechanism of action of GC, as well as of the long non coding RNA GAS-5 that has been found to regulate GC response. Moreover, the plasma levels of cytokines at disease onset and after 4 weeks of prednisone treatment were also evaluated. The studies in this thesis have hypothesized several candidates to predict GC response in children with INS, the results, being based on non-invasive methods, could lead to a turnaround in current treatment in childhood INS and could be relevant also for other pediatric populations treated with steroids.